Kesiapan Guru Dalam Mengadopsi Teknologi Cloud Untuk Pengelolaan Materi Ajar - Kadirun; Muh. Nurtanzis Sutoyo (GJET : Global Journal of Educational Technology, 2024)
The integration of cloud technology in education presents substantial prospects to improve the efficiency and efficacy of instructional material management. Nonetheless, the preparedness of educators, as the primary participants in the educational process, emerges as a pivotal aspect in the implementation of this technology. This study seeks to evaluate teacher preparedness for adopting cloud technology, assessed through four primary dimensions: digital competence, access to infrastructure, attitudes and motivation, and facilitating and obstructing factors. A descriptive quantitative approach was utilized, with data gathered via questionnaires administered to 35 educators. The findings suggest that the majority of teachers are classified as "Moderate," indicating sufficient yet suboptimal competencies. Certain educators fall into the "Low" category, mainly because to restricted access to technology and training. In contrast, educators in the "High" group exhibit significant ability to serve as mentors for their colleagues. This study advocates for the enhancement of training programs, accessibility to infrastructure, and incentive to facilitate the wider implementation of cloud technology